Bourdieu's capital accumulation: Exploring efforts to strengthen President Joko Widodo's political legitimacy - Zanuar Nur Hidayat (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2026)
The purpose of this article is to analyze the behavior of President Joko Widodo (Jokowi) in strengthening his political legitimacy based on Pierre Bourdieu's perspective. This article contributes to the development of Bourdieu's capital accumulation model in a factual context, especially by identifying the behavioral patterns of politicians in strengthening their political legitimacy. This article uses a qualitative research method through literature studies through various conceptual approaches and cases presented with analytical descriptions. This article begins the research by outlining Bourdieu's concept of capital accumulation and continues to analyze various types of capital in Jokowi's behavior. The findings of this article show that Jokowi's behavior in accumulating his capital to strengthen his political legitimacy began before his candidacy as President and continued to be strengthened during his term as President. Jokowi has a unique habitus compared to other politicians. This habitus is used to build cultural capital and strengthen social capital to build a national political network. Economic capital is slowly built through various policies that provide political legitimacy. Each of these capitals is accumulated into symbolic capital that provides a strong image as a popular leader. As a result, Jokowi succeeded in dominating the political arena and paving the way for power for his family, culminating in the election of Gibran as Vice President for the 2024-2029 period, despite various controversies and criticisms for weakening democracy.